2014
DOI: 10.1021/ac403868t
|View full text |Cite
|
Sign up to set email alerts
|

Single-File Nanochannel Persistence Lengths from NMR

Abstract: Crystalline solids composed of one-dimensional channels with cross-sectional dimensions below 1 nm represent an intriguing class of materials with important potential applications. A key characteristic for certain applications is the average open channel persistence length, i.e., the ensemble average distance from a channel opening to the first obstruction. This paper introduces an NMR-based methodology to measure this quantity. The protocol is applied to polycrystalline specimens of two different dipeptide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 47 publications
(63 reference statements)
1
27
0
Order By: Relevance
“…Finally, we also mention that it is well recognized that there are different temporal regimes of tracer diffusivity in finite SFD systems with conventional diffusion occurring for short times crossing over to SFD for moderate times, and potentially to center-of-mass diffusion for long times [11,15,17,21]. The latter crossover depends on location of the tagged particle within the pore, behavior reminiscent of the above position dependence on tracer diffusivity.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, we also mention that it is well recognized that there are different temporal regimes of tracer diffusivity in finite SFD systems with conventional diffusion occurring for short times crossing over to SFD for moderate times, and potentially to center-of-mass diffusion for long times [11,15,17,21]. The latter crossover depends on location of the tagged particle within the pore, behavior reminiscent of the above position dependence on tracer diffusivity.…”
Section: Introductionmentioning
confidence: 77%
“…Significantly for nanoporous materials, a number of experimental probes are sensitive to SFD dynamics and its impact on concentration profiles, so direct evidence of such anomalous dynamics can be obtained. These probes include pulsed-field-gradient (PFG) nuclear magnetic resonance (NMR) [7][8][9], hyperpolarized Xe 129 NMR spectroscopy [10,11] (which can monitor diffusion up to ∼10 s versus ∼100 ms for PFG NMR, thereby treating systems with lower mobilities), and infrared microimaging and interference microscopy for larger systems with dimensions ∼100 μm [12].…”
Section: Introductionmentioning
confidence: 99%
“…The 129 Xe HSTE data obtained in AV was found to be in essentially perfect compliance with a fully determined SFD model with no fitting parameters. 31,32 Whether or not nanotubular bisureas can serve as similarly ideal hosts, but with the advantage of variability in channel architecture, is one of several questions that is addressed in the present study.…”
Section: Articlementioning
confidence: 99%
“…Crystalline hydrophobic dipeptides of the VA-class 1, 2 are a type of ultramicroporous solids that has received considerable attention in recent years [3][4][5][6] . The structure of these molecular crystals is stabilised by H-bonds and hydrophobic interactions, being essentially the same for all VA-class dipeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when embedded in solvents of different colours, the crystals also become uniformly coloured 12 , indicating thorough solvent permeation into the pores. Recent NMR experiments have also shown that the pores in VA and AV dipeptide crystals typically span the entire crystal length 6 . Dipeptide crystals thus have incredibly open pores.…”
Section: Introductionmentioning
confidence: 99%